(untitled) (Al-Qamar, 2022)
Al-Shaikh Muhammad Mūsā Rawhānī is commonly known for his services and involvement in the field of Tafīr al-Quran, Hadith and Islamic Jurisprudence. He made huge literary contribution by merging Arabic language in his works along with numerous kinds of literature. He is an author of several books written on many topics of Islamic sciences and poetry like Hamd, Naat and Elegy (Marthia). This article predominately delivers contribution of Muhammad Mūsā Rawhānī, a prestigious person of Pakistan, his life and services particularly Arabic Elegy writing. He wrote elegy about Jamal Abdul Nasir, Mufti Mahmood, his teachers and friends.